The learning and transfer of science process skills in New Zealand secondary school distance education : a thesis presented in partial fulfilment of the requirements for the degree Master in Education, Massey University, Palmerston North - Latimer, Margaret Anne (Massey University, 1998)
This study investigates whether the science process skills of processing and interpreting scientific information, carrying out an investigation, communicating information and using information can be transferred across the strands of the Science in the New Zealand Curriculum (Ministry of Education, 1993b). The data were collected during the 1995 school year and was from a level 6 science course developed by the Correspondence School. Measurements of student performance were taken from moderated teacher-marked activities and were analysed using group means comparisons of each science process skill taught and pair-wise comparisons of students' performance. A representative population sample, chosen by using stratified random sampling, was surveyed on how they viewed the skills offered in the level 6 science course. The fulltime teachers who marked the level 6 science course in 1995, were also surveyed about the success of the course. The broad method used to conduct this research was illuminative evaluation. Results indicate, that while whole process skills such as carrying out an investigation may be transferable, other science process skills are more context bound and less likely to be transferred.
Keywords: New Zealand; Science -- Study and teaching (Secondary); Psychology of learning; Transfer of training